The higher serum uric acid to high-density lipoprotein cholesterol ratio is associated with increased risk of chronic obstructive pulmonary disease: result from NHANES 2011–2018 - Yunjia Bao; Jiangyuan Li; Zhiyu Wang; Linxi Lv; Mingyang Zhu (BMC Pulmonary Medicine)
Abstract Background Inflammation plays a significant role in the emergence and progression of chronic obstructive pulmonary disease (COPD). Uric acid to high-density lipoprotein cholesterol ratio (UHR) is a novel metabolic biomarker that is associated with the risk of inflammation. This study aimed to assess and evaluate COPD by calculating UHR. Methods The cross-sectional research utilized information from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2011 to 2018. To explore the link between UHR and COPD, a multivariate logistic regression analysis was conducted. In addition, effect analysis, smooth curve fitting, the receiver operating characteristic (ROC) curve analysis, Kaplan-Meier survival analysis, subgroup analysis, mediation analysis and sensitivity analysis were used to further explore the association between UHR and COPD. Results 688 patients were diagnosed with COPD among 9467 participants. After adjusting for interfering factors, logistic regression analysis revealed a notable correlation between UHR and COPD. Smooth curve fitting indicated a linear association between UHR and COPD. In addition, factors such as gender, smoking status, and hypertension were significantly associated with COPD. ROC curve analysis showed that the diagnostic accuracy of UHR was higher than that of Uric acid (UA) and High-density lipoprotein cholesterol (HDL-C). Higher UHR levels were associated with reduced survival. Subgroup analyses showed that gender, smoking status, and hypertension modified the association between UHR and COPD incidence. Mediation analyses identified C-reactive protein (CRP), triglycerides (TG) and phosphorus as potential mediators between UHR and COPD. Conclusions This research uncovered a notable correlation between UHR and COPD. These findings suggested that UHR could be a potential indicator for early diagnosis and intervention during COPD progression.